Playgroup Participation and Social Support Outcomes for Mothers of Young Children: A Longitudinal Cohort Study - Cunningham, Nadia; Lawrence, David; Zarb, David; Zubrick, Stephen R.; Hancock, Kirsten J (My University, 2015)
Objective: This study aimed to examine friendship networks and social support outcomes for mothers according to patterns of playgroup participation. Methods: Data from the Longitudinal Study of Australian Children were used to examine the extent to which patterns of playgroup participation across the ages of 3–19 months (Wave 1) and 2–3 years (Wave 2) were associated with social support outcomes for mothers at Wave 3 (4–5 years) and four years later at Wave 5 (8–9 years). Analyses were adjusted for initial friendship attachments at Wave 1 and other socio-demographic characteristics. Results: Log-binomial regression models estimating relative risks showed that mothers who never participated in a playgroup, or who participated at either Wave 1 or Wave 2 only, were 1.7 and 1.8 times as likely to report having no support from friends when the child was 4–5 years, and 2.0 times as likely to have no support at age 8–9 years, compared with mothers who persistently participated in playgroup at both Wave 1 and Wave 2. Conclusion: These results provide evidence that persistent playgroup participation may acts as a protective factor against poor social support outcomes. Socially isolated parents may find playgroups a useful resource to build their social support networks.
PLOS One
Keywords: Families -- Mothers; Relationships -- Formation; Relationships; Families and relationships; Relationships; Families; Formation; Mothers; Families and relationships